ZIRCON U-Pb AGES, Hf ISOTOPIC CHARACTERISTICS AND THEIR IMPLICATIONS OF THE EARLY PALEOZOIC GRANITES IN THE NORTHEASTERN DA HINGGAN MTS., NORTHEASTERN CHINA - Ge W.C.; Sui Z.M.; Zhang J.H.; Xu X.C.; Cheng R.Y.; Wu F.Y. (My University, 2007)
The Paleozoic granites in the Ergun block, exposed in the northeastern Da Hinggan Mts., northeastern China, are of I-type. Zircon U-Pb dating by LA-ICPMS technique indicates that the Shibazhan, Neihe and Baiyinna plutons were emplaced with ages of 499 ± 1,500 ± 1 and 460 ± 1Ma; whereas the Chalabanhe pluton was formed by several pulses with age between 465-481 Ma. Considering other previously reported age data, it is proposed that the granitic magmatism in the northeastern Da Hinggan Mts. during the Early Paleozoic took place at 460-50OMa. Zircon Hf analyses conducted by LA-MC-ICPMS show that these granites have εHf(t) values of +1.5 ∼ +3.8 with Hf modal ages of 1.1 ∼ 1.4Ga, indicating that the crust in the Ergun block was extracted from mantle during Meso-Neoproterozoic, which is much different from the Xing'an block to the south, in that it shows a characterized Phanerozoic crustal age.
Keywords: EARLY PALEOZOIC; GRANITE; HF ISOTOPE; NORTHEASTERN DA HINGGAN MTS., NORTHEASTERN CHINA; ZIRCON U-PB AGE; Paleozoic::Cambrian; Палеозой::Кембрийская